2022
DOI: 10.3389/fphar.2022.833189
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Thresholds for Beta-Lactam Antibiotics: A Story of Mouse Versus Man

Abstract: Beta-lactams remain a critical member of our antibiotic armamentarium and are among the most commonly prescribed antibiotic classes in the inpatient setting. For these agents, the percentage of time that the free concentration remains above the minimum inhibitory concentration (%fT > MIC) of the pathogen has been shown to be the best predictor of antibacterial killing effects. However, debate remains about the quantity of fT > MIC exposure needed for successful clinical response. While pre-clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 67 publications
0
24
2
Order By: Relevance
“…Pharmacodynamically, like conventional β-lactams, the %ƒT > MIC has been described as the optimal PK/PD index associated with the efficacy of NBLA. However, the optimal percentage to target is still controversial [ 29 ]. Preclinical studies of conventional β-lactams suggested that approximately 1–2 log 10 reductions of colony-forming units (CFU) can be achieved with <100%ƒT > MIC, depending on the used antimicrobial (i.e., 40%, 50–60%, and 50–70%ƒT > MIC for carbapenems, penicillins, and cephalosporins respectively) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacodynamically, like conventional β-lactams, the %ƒT > MIC has been described as the optimal PK/PD index associated with the efficacy of NBLA. However, the optimal percentage to target is still controversial [ 29 ]. Preclinical studies of conventional β-lactams suggested that approximately 1–2 log 10 reductions of colony-forming units (CFU) can be achieved with <100%ƒT > MIC, depending on the used antimicrobial (i.e., 40%, 50–60%, and 50–70%ƒT > MIC for carbapenems, penicillins, and cephalosporins respectively) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the utilization of conventional PD thresholds (i.e., 40–60%ƒT > MIC) could be argued for NBLA, especially when considering the concentrations of BLIs, for the most part, BLIs by their own are inactive against invading pathogens [ 30 ]. The PD targets of such inhibitors (i.e., threshold of concentration (C T ) for avibactam/tazobactam and 24 h area under the free concentration–time curve ( f AUC 24 /MIC) for vaborbactam/relebactam) reflect the required concentrations to restore β-lactam activity, thus leaving PD targets of β-lactam backbone consistent with the PD targets described above for the severely sick population [ 29 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most β-lactams are considered to be maximally effective when their free concentration at the site of infection is four times above the MIC (fT > MIC) for at least 40-70% of the dosing interval [19,20]. When these concepts are applied to cephalexin, drug concentrations would need to be at 16 μg/mL for MSSA (4 times the observed median MIC).…”
Section: Discussionmentioning
confidence: 99%
“…However, dissemination of antimicrobial resistance around the world has been one of the biggest threats to global public health, with a growing threat from infectious diseases, especially to critically ill infections or immunocompromised patients. Accordingly, the early qualitative and quantitative detection of drug-resistant bacteria is of great significance for the efficient diagnosis and treatment of drug-resistant bacteria infection. One of the main resistance mechanisms is the production of β-lactamase (Bla).…”
Section: Introductionmentioning
confidence: 99%